A case report of neurological adverse events caused by short-term and low-dose treatment of mitotane: The role of therapeutic drug monitoring. Issue 40 (2nd October 2020) - Liu, Xin; Fu, Qiang; Tang, Yan; Deng, Jian-hua; Mei, Dan; Zhang, Bo
Abstract: Rationale: Low-dose mitotane has been widely used for many decades in patients with advanced adrenocortical carcinoma (ACC), which exhibited good safety profiles compared with the high-dose regimen. The clinical efficacy and toxicity of mitotane are closely related to its plasma concentration, and therapeutic drug monitoring (TDM) is recommended. Until now, no severe adverse drug reaction (ADR) related to the toxic plasma level after a short-term treatment of low-dose mitotane has been published. Patient concerns: A 50-year-old Chinese female presented with severe neurological adverse events related to a toxic plasma levels of 42.8 mg/L after 4 months treatment of low-dose mitotane. Diagnoses: During the course of therapy, no other medication could cause neurological adverse events. Therefore, we suspected a high sensitivity to the side effect of mitotane related to a toxic plasma level. Interventions: Treatment of mitotane was stopped. Outcomes: The trough plasma concentration of mitotane decreased to 18.7 mg/mL after one and a half months, and the neurological symptoms gradually improved after drug discontinuance. Lessons: The present case provides the first report of severe neurological adverse events induced by the short-term use of low-dose mitotane for adjuvant treatment in a patient with ACC, indicating that potentially severe ADR can also occur when using low-dose regimen in the early stage of treatment. TDM and early recognition could result in a favorable outcome.